The Snail-killing Flies (Diptera: Sciomyzidae) of West Africa - Knutson, Lloyd V.; Deeming, John C.; Ebejer, Martin J. (Zootaxa, 2018)
A review of the West African “snail-killing flies” or “marsh flies” (Sciomyzidae) shows that the fauna is not as dominated by the generally aquatic, predaceous genus Sepedon as was previously considered. Twenty species in seven genera, including three new species, Colobaea occidentalis, Pteromicra zariae and Sepedonella castanea are recorded. The Holarctic-Oriental genera Colobaea and Pteromicra are documented from Africa south of the Sahara for the first time. Biogeographical analyses based on the discovery of “Palaearctic” genera of Diptera south of the Sahara, faunal connections, and dispersal routes are presented. A key for identification and illustrations of diagnostic characters for some species are included.